80 Should Military Recruits be Screened with a 12-lead ECG in addition to History and Physical Examination?. (6th June 2015) - Cannie, Douglas; Cox, Andrew; Chamley, Rebecca; Parsons, Iain; Behr, Elijah; Wilson, Duncan; Sharma, Sanjay; Bogle, Richard
Abstract : Aim: To establish the prevalence of cardiac conditions in British Army recruits in whom a murmur is detected. Methods: Recruits were screened with a standardised questionnaire and physical examination by military occupational physicians. Those with cardiac symptoms, a history suspicious for cardiac disease, or with hypertension, were referred to their civilian Primary Care Doctor for further investigation. Those recruits with an isolated murmur on auscultation underwent an ECG, echocardiogram and cardiology review in a military clinic and are the subject of this study. Results: Over a seven year period, 11420 consecutively referred recruits aged 15–32 years (89% male) were evaluated. Significant valve disease was identified in 146 (1.28%) recruits. Bicuspid aortic valve occurred in 124 (1.09%) recruits of which 67.7% demonstrated some form of valvular dysfunction, aortopathy, coarctation of the aorta or left ventricular dysfunction. Cardiac disease was strongly suspected or diagnosed in a total of 921 recruits (positive predictive value (PPV) 8.06%). Of these recruits, 298 (32.4%) had cardiac conditions associated with an increased risk of sudden cardiac death (SCD) including 98 (10.6%) with probable cardiomyopathy; 22 (2.4%) with accessory pathways; and 30 (3.3%) with possible channelopathies (see Table 1 ). Males accounted for 91.9% of those with cardiac abnormalities but no significant male disease preponderance was observed (p = 0.117). The remainder of the recruits had a range of ECG and echocardiographic abnormalities not typically associated with SCD. Discussion: These results show that an isolated murmur, detected by military occupational physicians as part of a cardiac screening program, has a low PPV for the detection of significant valve disease in asymptomatic individuals. The screening program incidentally detected a larger cohort of recruits with potentially serious underlying cardiac abnormalities, resulting in deferral of military service. Most of these conditions are not classically associated with a cardiac murmur and were diagnosed from ECG or echocardiography. Without these investigations, it is unlikely they would have been detected. Therefore, the addition of routine ECG, and possibly echocardiography to the British Army cardiac screening protocol should be considered. This approach would improve the detection rate of potentially serious, non-valvular cardiac disease requiring further evaluation before military service can be approved. In military populations, cardiac conditions are a potentially preventable cause of mortality and morbidity. It is believed that individuals with these conditions can be readily identified using a standardised history and physical examination. However, there is growing evidence that addition of routine 12-lead ECG increases the sensitivity for detection of underlying cardiac abnormalities. Current guidelines on pre-participation screening in athletes recommend this approach.